2004
DOI: 10.1017/s0012162204000908
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of selective muscle-release surgery for children with cerebral palsy: longitudinal and stratified analysis

Abstract: The purpose of this study was to determine the effectiveness of muscle-release surgery for children with cerebral palsy (CP) using longitudinal and stratified analysis. Twenty-five children with CP (15 females, 10 males; age range 4 to 16 years; mean age 8 years 2 months, SD 3 years 2 months) were selected from five treatment centres in Japan. Twenty-two children had spastic diplegia, two had spastic quadriplegia, and one had athetospastic quadriplegia. Motor function for each child was assessed using the Gros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 13 publications
0
17
0
3
Order By: Relevance
“…Previous investigators have reported mixed results with regard to changes in GMFM scores after single-event multilevel surgery 10,13,14,42 . Kondo et al 10 reported increases in GMFM-66 scores after soft-tissue procedures in a younger cohort of children with cerebral palsy (GMFCS levels I through IV).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous investigators have reported mixed results with regard to changes in GMFM scores after single-event multilevel surgery 10,13,14,42 . Kondo et al 10 reported increases in GMFM-66 scores after soft-tissue procedures in a younger cohort of children with cerebral palsy (GMFCS levels I through IV).…”
Section: Discussionmentioning
confidence: 98%
“…Kondo et al 10 reported increases in GMFM-66 scores after soft-tissue procedures in a younger cohort of children with cerebral palsy (GMFCS levels I through IV). Their study was uncontrolled and included children with GMFCS level IV, who are not expected to be capable of longterm ambulation 42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GMFM is frequently used to evaluate the effects of various interventions in children with CP, such as intensive physiotherapy, [11][12][13][14] botulinum toxin treatment, 15 selective dorsal rhizotomy, 16 and orthopaedic surgery. [17][18][19] The GMFM is a test specially designed and validated for measuring gross motor function and the change over time in children with CP. The test contains 88 items of gross motor function distributed over five dimensions: lying and rolling; sitting; crawling and kneeling; standing and walking; and running and jumping.…”
mentioning
confidence: 99%